Corporate social responsibility in Spanish audiovisual corporations. An analysis of RTVE, Atresmedia and Mediaset - Díaz Campo, Jesús (2020)
This research analyzes the corporate social responsibility (CSR) reports of the main audiovisual companies in Spain (Radio Televisión Española, Atresmedia and Mediaset España). The main objective is to determine the level of implementation of CSR policies in each one of them. We use content analysis methodology. It consists of 14 indicators and it is based of one previous research (Campos, 2013). The results show that there is a greater level of implementation in the public corporation than in the private ones.